2015
DOI: 10.1097/qai.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research

Abstract: Background:Early infant male circumcision (EIMC) is a potential key HIV prevention intervention, providing it can be safely and efficiently implemented in sub-Saharan Africa. Here, we present results of a randomized noninferiority trial of EIMC comparing the AccuCirc device with Mogen clamp in Zimbabwe.Methods:Between January and June 2013, eligible infants were randomized to EIMC through either AccuCirc or Mogen clamp conducted by a doctor, using a 2:1 allocation ratio. Participants were followed for 14 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…The follow-up study (conducted in 2013) explored actual acceptability of EIMC among parents who had either opted or declined to have their newborn son circumcised. The second study was nested within a trial that assessed the feasibility, safety, acceptability and cost of rolling out EIMC using devices in Zimbabwe, described in detail elsewhere [9, 16, 22]. In both studies, researchers explored among other issues, decision-making around EIMC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up study (conducted in 2013) explored actual acceptability of EIMC among parents who had either opted or declined to have their newborn son circumcised. The second study was nested within a trial that assessed the feasibility, safety, acceptability and cost of rolling out EIMC using devices in Zimbabwe, described in detail elsewhere [9, 16, 22]. In both studies, researchers explored among other issues, decision-making around EIMC.…”
Section: Methodsmentioning
confidence: 99%
“…The program aims to reach 1.3 million 15-29 year-olds by 2017/18. Zimbabwe also intends to offer EIMC alongside VMMC [15, 16, 22]. Since large-scale EIMC for HIV prevention, or indeed for other reasons, has never been practiced in Zimbabwe or more widely in Southern Africa, there is a dearth of literature on EIMC decision-making within this context.…”
Section: Introductionmentioning
confidence: 99%
“…Other circumcision sequelae of sufficient severity to require emergency room evaluation or hospital admission and contribute toward allostasis include infection, urinary retention, inflammatory redness and swelling ascribed to healing (86, 87), and amputation/necrosis of the glans (88). Behavioral abnormalities, such as eating disturbance and disturbed sleep, are also the consequence of pain exposure (89).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative circumcision pain of ample severity to require analgesia is expected for about 10 days for healing with incomplete wound healing past day 14 seen in up to 6% of infants depends on the device used to amputate the foreskin (88), which is also associated with various adverse events (56, 90). The overall complication rate for circumcision ranges from 0.2 to 10% with many USA physicians performing the procedure without formal training, being unaware of contraindications, and incapable of handling post-op complications (56, 91, 92).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted within the region have shown poor concordance between hypothetical and actual EIMC acceptability. In Zambia and Zimbabwe, actual uptake was lower than previously suggested by hypothetical acceptability studies (11% vs. 97% and 12% vs. 60%, respectively) [1516, 19, 38–39]. Given the low levels of knowledge or experience of EIMC found in the FGDs and KIIs, it is unclear whether or not the high hypothetical acceptability will translate into actual uptake once EIMC is introduced.…”
Section: Discussionmentioning
confidence: 83%